The difficulties of determining the notion of organized crime - Mrvić-Petrović Nataša (Temida)
The author emphasizes the most significant difficulties and disagreements in determining the notion of organized crime, which, on one hand, come as a result of a complexity and dynamism of a contemporary organized crime, and on the other hand, may lead to passing the inadequate legislation and/or the failure of actions against the organized crime. Pointing out to the differences between contemporary organized crime and theoretical definitions of it from the first decades of the 20th century, the author concludes that the answer to the organized crime should be systematic, and need to include the rule of law and the principles of division and control of state power. The author suggests that the changes are necessary within the present criminal legislature of Serbia. In these changes the emphasis need to be on the protection of victims rather than on special legal solutions and special court, prosecution and police units for suppression of organized crime.